Employee stock options - Huddart, Steven (Journal of Accounting and Economics, 1994)
This paper examines the valuation of employee stock options (ESOs). Because ESOs are inalienable, the employee's optimal exercise policy differs from the policy a naive reading of the finance literature would suggest. The employee prefers to exercise options before maturity under certain conditions on risk aversion, investment opportunities, and wealth. Since the ESOs' cost to the employer depends on the employee's exercise policy, this finding has implications for changes to the accounting treatment of ESOs under this finding has implications for changes to the accounting treatment of ESOs under consideration by the Financial Accounting Standards Board. Numerical examples suggest the employer's cost is much less than the options' Black-Scholes value.